Male genital injuries in infants caused by the bite of pet pups: Case series and literature review - Pamposh Raina; Girish Kumar Sharma; Kailash Chander Barwal; Manjeet Kumar; Sanjeev Chauhan (Wolters Kluwer Medknow Publications, 2022)
Injuries to male genitalia of infants due to bite of a pet pup are a rare occurrence. Few dog bite injuries to the genitalia of male infants have been reported, however, similar injuries have not been reported by the bite of pet puppies. Male genital injury in three male infants aged 8, 10, and 11 months, by the bite of pet puppies aged 1-2 months, ranged from avulsion of penile and part of scrotal skin with loss of both testes in case 1, a near circumferential laceration of penile skin at the base of penis with scrotal laceration in case 2, and laceration in mid penile shaft resulting in degloving and complete transaction of distal penile urethra with scrotal laceration in case 3. All these infants were appropriately managed surgically (case 1 and 3) and conservatively (case 2) and were given thorough toileting of wound, antibiotics, prophylaxis for tetanus and rabies. Some of these injuries may require complex surgical procedures to reconstruct the male genitalia. Timely management with aggressive intent and conserving the local tissue is the key to success. We describe a case series of injury to the external genitalia of three male infants by the bite of pet puppies, their possible predisposing factors, treatment, and follow-up. A case report and series like this have not been reported in literature so far to the best of our knowledge.